Detection and sequencing of Zika virus in normocephalic newborns with congenital Zika infection - Breno Lima de Almeida (Elsevier, 2022)
ABSTRACT: Fourteen asymptomatic normocephalic newborns with confirmed congenital Zika infection were investigated. All newborns presented Zika virus (ZIKV) positivity on reverse transcriptase polymerase chain reaction. Following ZIKV-specific NS5 gene fragment sequencing in one child, phylogenetic analysis revealed that this isolate belonged to the Asian genotype, and clustered closely with other sequences previously isolated in north-east and northern regions of Brazil.